2008
DOI: 10.1152/ajpregu.00716.2007
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and cachexia inApcMin/+mice

Abstract: The Apc(Min/+) mouse has a mutation in the Apc tumor suppressor gene and develops intestinal polyps, beginning at 4 wk of age. This mouse develops cachexia by 6 mo, characterized by significant loss of muscle and fat tissue. The purpose of the present study was to determine the role of circulating interleukin-6 (IL-6) and the polyp burden for the development of cachexia in Apc(Min/+) mice. At 26 wk of age, mice exhibiting severe cachectic symptoms had a 61% decrease in gastrocnemius muscle weight, complete los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
275
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(295 citation statements)
references
References 42 publications
19
275
0
1
Order By: Relevance
“…It has been reported that IL6 −/− APC Min/+ mice have moderately attenuated polyposis (31). To test the notion that MC derived IL6 was contributing to polyposis, we lethally irradiated 6-week-old APC Δ468 mice and reconstituted them with bone marrow (BM) from IL6 −/− mice or from wt control mice.…”
Section: Il6 Focal Mastocytosis and Polyposis Are Independent Of Bonementioning
confidence: 99%
“…It has been reported that IL6 −/− APC Min/+ mice have moderately attenuated polyposis (31). To test the notion that MC derived IL6 was contributing to polyposis, we lethally irradiated 6-week-old APC Δ468 mice and reconstituted them with bone marrow (BM) from IL6 −/− mice or from wt control mice.…”
Section: Il6 Focal Mastocytosis and Polyposis Are Independent Of Bonementioning
confidence: 99%
“…These expression level changes of COX-2, iNOS, and adipocytokines, especially iNOS, could be associated with intestinal polyp development in Min mice. Indeed, it has been reported that iNOS inhibition, Pai-1 inhibition, COX-2 inhibition, and IL-6 knock out suppressed intestinal polyp development in Min mice (31,38,39,40). It has also been reported that 100-ppm atorvastatin treatment in Min mice slightly, but not significantly, reduced the activity and expression levels of COX-2 in the intestinal polyp (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-6 is primarily produced following an immune response, convincing evidence demonstrates that IL-6 is also involved in satellite cell-mediated muscle hypertrophy and regeneration. Chronic systematic elevation of IL-6 leads to muscle atrophy in aging and disease states (29,212; reviewed in Ref. 154).…”
Section: Systemic Milieumentioning
confidence: 99%